2014
DOI: 10.2478/amm-2014-0061
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Tribological Properties of the Copper Matrix Composite Materials Containing Lubricating Phase Particles

Abstract: The paper presents results of the studies into influence of individual particles of lubricating phase on microstructure and tribological properties of copper based composite materials for slide bearings. The studied material was composed of copper alloys with lubricating phase particles, e.g. in a form of graphite and glassy carbon. The metallic matrix of composite materials consisted of Cu-Sn type alloys. Production of the examined materials included processes with complete or partial participation of liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Another variant of GC carbon applications is metal matrix composites where GC is employed in the form of particles (GCp). In that case, aluminium alloy [3] and copper alloy matrixes can be used [4]. The author's own investigations with composites processed by powder metallurgy (PM) methods [5] showed that GCp can also be employed successfully with the magnesium-aluminium-zinc alloy AZ91 as the matrix but that technological solution generates a limitation of the final product size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Another variant of GC carbon applications is metal matrix composites where GC is employed in the form of particles (GCp). In that case, aluminium alloy [3] and copper alloy matrixes can be used [4]. The author's own investigations with composites processed by powder metallurgy (PM) methods [5] showed that GCp can also be employed successfully with the magnesium-aluminium-zinc alloy AZ91 as the matrix but that technological solution generates a limitation of the final product size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…The application of glassy carbon particles [1,2] as a component of a metal matrix composite can be a way of modifying the tribological properties of metal-based materials [3][4][5] and it is proposed for composites with matrixes made of aluminium and magnesium alloys. However, the properties of the new materials designed and obtained under precisely controlled conditions in the laboratory scale must be verified in the case when they are manufactured in the industrial scale.…”
Section: Introductionmentioning
confidence: 99%